Development of Fun Thinkers Book as an Interactive Learning Media for Science Learning - Subekti, Alfian Ichsan; Winarno, Ahmad; Kusyairi, Latif (Aspirasi Masyarakat Intelektual Islam Nusantara, 2025)
Science education is crucial in developing students' critical thinking and analytical skills. However, conventional teaching methods often fail to engage students effectively, leading to difficulties in understanding scientific concepts. This study aims to develop and evaluate the Fun Thinkers Book as an interactive instructional medium for fourth-grade science students at MI Salafiyah Sidorenggo, Malang Regency. Utilizing the ADDIE model, the research followed five phases: Analysis, Design, Development, Implementation, and Evaluation. The validity of the Fun Thinkers Book was assessed through expert validation, obtaining scores of 90% from subject matter experts, 86% from media experts, and 88% from classroom teachers, categorizing it as highly valid. The practicality test, conducted through field trials, revealed that 84.8% of students found the book engaging and easy to use, confirming its high practicality. The results indicate that the Fun Thinkers Book is a valid and practical instructional tool that enhances students' engagement and comprehension in science education. Future research should explore its adaptability across different grade levels and subjects to further improve its educational impact.